(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2011)
This paper discusses the relationship between learning the Qur'an by heart and academic achievement, language learning and linguistic creativity. It also attempts to arrive at Qur'an-grounded foundations for language acquisition theory. This opinion paper outlines the basis from which to consider the Qur'an not only as a book of religious teachings but also as a linguistic miracle for Arabs. In this vein, the paper considers available research evidence documenting the relationship between language creativity and learning the Qur'an and also establishes a relationship between learning the Qur'an and scholastic achievement in other school subjects. Research indicates that the Qur'an can be a strong source for teaching thinking methods and creativity. The paper re-considers language acquisition in the light of the Qur'an and research investigations into its effects on creative language learning based on relevant scholarly Arabic writings. The paper ends with pedagogical notes and implications for L1 and L2 learning.